Sensory characteristics of Slovenian honey - Terezija GOLOB; Jasna BERTONCELJ; Vida ŠKRABANJA (Acta Agriculturae Slovenica, 2002)
The objective of the present study was to assess the sensory quality of Slovenian honey. Three sensory attributes: colour, odour and aroma of 293  honey samples were evaluated by an experienced and trained panel of six assessors. Samples were collected in years 1998 to 2000 and classified to five assorted (acacia, chestnut, fir, lime and spruce) and four unsorted (flower, forest, blend and Metcalfa pruinosa) honeys. The analysis of variance showed that between honey types the differences in colour and odour were statistically significant. The honeys sensory characteristics were generally not influenced by the production year and different seasonal climatic conditions. Sensory evaluation can overcome the limitations of chemical and pollen analyses and serve as an appropriate tool for honey type authentication.